The extinct marine megafauna of the Phanerozoic - Catalina Pimiento (Cambridge Prisms: Extinction, 2024)
The modern marine megafauna is known to play important ecological roles and includes many charismatic species that have drawn the attention of both the scientific community and the public. However, the extinct marine megafauna has never been assessed as a whole, nor has it been defined in deep time. Here, we review the literature to define and list the species that constitute the extinct marine megafauna, and to explore biological and ecological patterns throughout the Phanerozoic. We propose a size cut-off of 1 m of length to define the extinct marine megafauna. Based on this definition, we list 706 taxa belonging to eight main groups. We found that the extinct marine megafauna was conspicuous over the Phanerozoic and ubiquitous across all geological eras and periods, with the Mesozoic, especially the Cretaceous, having the greatest number of taxa. Marine reptiles include the largest size recorded (21 m; Shonisaurus sikanniensis) and contain the highest number of extinct marine megafaunal taxa. This contrasts with today’s assemblage, where marine animals achieve sizes of >30 m. The extinct marine megafaunal taxa were found to be well-represented in the Paleobiology Database, but not better sampled than their smaller counterparts. Among the extinct marine megafauna, there appears to be an overall increase in body size through time. Most extinct megafaunal taxa were inferred to be macropredators preferentially living in coastal environments. Across the Phanerozoic, megafaunal species had similar extinction risks as smaller species, in stark contrast to modern oceans where the large species are most affected by human perturbations. Our work represents a first step towards a better understanding of the marine megafauna that lived in the geological past. However, more work is required to expand our list of taxa and their traits so that we can obtain a more complete picture of their ecology and evolution.